2019
DOI: 10.1021/acsapm.9b00631
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Organic Probe Decorated Water-Soluble Polymer Chains on Natural Fibers for Selective Detection and Efficient Removal of Hg2+ Ions in Pure Aqueous Media

Abstract: Developing dual-functional materials that can simultaneously detect and remove toxic heavy metal ions is of practical importance but still remains a challenging task. Herein, an ionrecognizable material, MA−SAPQA@NFs, was facilely fabricated through covalent grafting of salicylaldehyde-containing polymeric quaternary ammonium (SAPQA) chains onto the lotus seedpodderived natural fibers (NFs), followed by decoration with 2mercaptoaniline (MA). Several remarkable features for MA− SAPQA@NFs, which could rarely be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Moreover, POSS-Se was determined to have a capacity of 952 mg g −1 of Hg 2+ (the capacity of POSS-Se (HCl) is 907 mg g −1 , which was determined under the same method to that of POSS-Se). This value is higher than most reported Hg 2+ adsorbents, such as NH 2 -MIL-53(Al) (153.85 mg g −1 ) [42], MA−SAPQA@NFs (218.21 mg g −1 ) [43], sulfur-doped porous reduced graphene oxide (829.27 mg g −1 ) [47], SiO 2 -G0-SA∼SiO 2 -G2.0-SA (363.07 mg g −1 ) [51], and TAPB-BMTTPA-COF (734 mg g −1 ) [53], although some of them have lower LODs compared to that of POSS-Se (HCl) ( Table 1). experiment was performed by adsorbing Hg 2+ ions (1000 ppm) using POSS-Se and the acid product POSS-Se (HCl) as the adsorbents as suspension in water (1 mg mL −1 ).…”
Section: Adsorption Of Hg 2+ Ions By Poss-sementioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, POSS-Se was determined to have a capacity of 952 mg g −1 of Hg 2+ (the capacity of POSS-Se (HCl) is 907 mg g −1 , which was determined under the same method to that of POSS-Se). This value is higher than most reported Hg 2+ adsorbents, such as NH 2 -MIL-53(Al) (153.85 mg g −1 ) [42], MA−SAPQA@NFs (218.21 mg g −1 ) [43], sulfur-doped porous reduced graphene oxide (829.27 mg g −1 ) [47], SiO 2 -G0-SA∼SiO 2 -G2.0-SA (363.07 mg g −1 ) [51], and TAPB-BMTTPA-COF (734 mg g −1 ) [53], although some of them have lower LODs compared to that of POSS-Se (HCl) ( Table 1). experiment was performed by adsorbing Hg 2+ ions (1000 ppm) using POSS-Se and the acid product POSS-Se (HCl) as the adsorbents as suspension in water (1 mg mL −1 ).…”
Section: Adsorption Of Hg 2+ Ions By Poss-sementioning
confidence: 60%
“…POSS-Se (HCl) exhibits a high sensitivity towards Hg 2+ with a low LOD of 8.48 ppb (Figure 4c). The acquired value is comparable to or higher than many reported sensors [39], such as Fe 3 O 4 @TiO 2 -L (L=2,6-bis(2-thienyl)pyridine, 1.40 ppm) [40], thioether-based fluorescent covalent organic framework (COF-LZU8, 25.0 ppb) [41], metal-organic framework (NH 2 -MIL-53(Al), 30.13 ppb (0.15 µM)) [42], nature fibers modified by polymer chains (MA−SAPQA@NFs, 16.72 ppb (0.08 µM)) [43], silica modified by an anthracene excimer (SiO 2 @PBATPA, 37 ppb) [44], and vesicular chemical sensor (10.64 ppb (53.0 nM)) [45], but lower than some sensors such as rhodamine B selenolactone (4.62 ppb (53.0 nM)) [37], fluorescent phosphane selenide (0.18 ppb) [46], and sulfur-doped porous reduced graphene oxide [47] ( Table 1). The lower performance may be due to the heterogenous detection by POSS-Se (HCl), which is insoluble in water, in contrast to the homogenous detection by most sensors, which are commonly soluble in water.…”
Section: Detection Of Hg 2+ Ions By Poss-sementioning
confidence: 99%
“…It was suggested that the initial natural porous structure of LSP for ZnCl 2 and FeCl 3 loading played an important role in the morphology of Fe- and Zn-based products. LSP contains natural cellulose fibers [ 84 ]. Wire-like morphology may, therefore, result from crystallization in an extremely narrow fibrous matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The saturation adsorption ( q max ) of the precursor polymers varied from 128 to 216 mg/g, while the final polymers showed a much higher q max of 374–425 mg/g, which was comparable to some reported polymers (Table ). , The much higher Hg 2+ capacities of the MA-based polymers should be from the fact that they had much higher V micro and N content. TPE–PMDA–MA possessed the highest Hg 2+ uptake of 425 mg/g at 298 K. Its highest S BET , V micro , and abundant N groups should give great positive contributions.…”
Section: Resultsmentioning
confidence: 99%